Novel Nanocatalysts for Sustainable Hydrogen Production from Renewable Resources - Verma Vikas; Joshi Abhishek; Kalra Simran; Singh Amanveer; Singh Amanveer; Mohan Chandra (E3S Web of Conferences, 2024)
This research delves into the development, manufacturing, and assessment of nanocatalysts with the purpose of producing hydrogen sustainably from renewable resources. Using the sol-gel, hydrothermal, co-precipitation, and solvothermal processes, four distinct catalysts with the labels A, B, C, and D were created, respectively. The rate of hydrogen generation, activation energy, turnover frequency, and surface area were used to assess the catalytic performance. Catalyst A outperformed Catalyst B in terms of hydrogen generation rate, with a 10% increase to 50 mmol/g/hr. Moreover, Catalyst A showed superior reaction kinetics with a lower activation energy of 50 kJ/mol. With a turnover frequency of 0.02 s^-1, catalyst C had the highest activity, indicating a higher catalytic activity per active site. Furthermore, with a surface area of 120 m^2/g, Catalyst D offered the most active locations for reactions that produce hydrogen. Environmental impact analyses showed that various catalysts used varied amounts of resources and produced varying amounts of waste. With 950 liters of water used and 45 kWh of energy consumption, Catalyst B showed the lowest use, whereas Catalyst D produced the least amount of chemical waste (6 kg). The results of the stability tests showed that the durability of the catalysts varied, with Catalyst D showing the maximum stability after 100 cycles. Overall, the results emphasize how crucial catalyst design and synthesis techniques are to the development of effective and long-lasting hydrogen generation technologies. To optimize catalyst compositions, improve stability, and scale up manufacturing for real-world applications in renewable energy systems, further research is necessary.